2018
DOI: 10.1142/s1363919618500123
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Training and Innovation in Companies

Abstract: The purpose of this paper is to research the effect of training on innovation in a sample of Colombian industrial companies. To this effect, an analysis of the relationship between training and each one of its dimensions (planning, alignment, assessment and resources) and the types of innovation (technological and non-technological) was carried out. These relationships were studied in 78 companies, using multivariable analysis techniques, such as cluster analysis, analysis of variance (ANOVA) and regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Therefore, they concluded that the competence of staff is highly effective on the company's success in developing new products and services. In this context, the company should choose the competent ones in the selection of personnel (Naranjo‐Valencia et al 2018; Rodríguez‐López & Souto 2019). Similar to these studies, Fu (2018), Hughes et al (2019) and Li et al (2018) also underlined the significance of this issue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, they concluded that the competence of staff is highly effective on the company's success in developing new products and services. In this context, the company should choose the competent ones in the selection of personnel (Naranjo‐Valencia et al 2018; Rodríguez‐López & Souto 2019). Similar to these studies, Fu (2018), Hughes et al (2019) and Li et al (2018) also underlined the significance of this issue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, associating the results with the new institutional economy (Williamson 1975;Johannessen 2008) is one way to expand the research reported here. Third, further studies should distinguish between different types of innovation and assess their impact on performance (Naranjo-Valencia et al 2018;Castillo-Apraiz et al 2020a). Similarly, instead of capturing personnel training at a global level, further studies could for example assess how personnel training within specific areas -such as R&D-impacts performance.…”
Section: Limitations and Directions For Further Researchmentioning
confidence: 99%
“…Innovative and creative practices, which stimulate employees, improve their learning and performance conditions and guide their decisions and actions, need to be designed and implemented in companies (Chen and Huang, 2009;Tan and Nasurdin, 2011). In this line, there are few studies that provide empirical evidence of the need for new, creative and innovative training practices (Naranjo-Valencia et al, 2018). Among the research gaps, the authors also identify the need to study specific practices as in Naranjo-Valencia et al (2018), who evaluated training as alignment, planning, resources and assessment, since most of the literature understands training as a general practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, there are few studies that provide empirical evidence of the need for new, creative and innovative training practices (Naranjo-Valencia et al, 2018). Among the research gaps, the authors also identify the need to study specific practices as in Naranjo-Valencia et al (2018), who evaluated training as alignment, planning, resources and assessment, since most of the literature understands training as a general practice. This paper consequently focuses on four specific practices (employee training for creativity and innovation (C&I), formalised idea generation sessions, work time (WT) devoted to creativity and innovation and WT spent on talent development programmes), called training and development for creativity and innovation (TD4CI) practices, to determine if and to what extent adopting these practices affects firm performance, specifically innovation and financial performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation